Kenakalan Remaja dalam Perspektif Filsafat Sosial Thomas Hobbes - Agi Pratama; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
This study aims to discuss juvenile delinquency according to the social philosophy perspective of Thomas Hobbes. This research study uses a descriptive qualitative method with a documentation study approach. Qualitative research methods are tools for exploring and understanding the meanings that a number of individuals or groups of people ascribe to social or humanitarian issues. Documentation study is a data collection technique that comes from someone's writing, drawing or work. Juvenile delinquency is an act or action that violates the norms, rules or laws in society that is committed at a young age or during the transition from childhood to adulthood. Factors causing Juvenile Delinquency are social pathological symptoms in adolescents caused by a form of social neglect which ultimately leads to deviant behavior. Teenage age is a very vulnerable age because the characteristics of adolescence are emotional instability due to many problems, because emotionality dominates over abilities so that adolescents are less able to accept other people's opinions. This statement is in accordance with the expression of Thomas Hobbes in his theory "Homo Homini Lupus" that humans are wolves for other humans. This proverb seems to adequately represent someone's brutality towards other people so that with this situation it seems as if humans want to pounce on their prey. If it is associated with juvenile delinquency, it occurs because of desires that cannot be controlled so that the person gets lost in desires that violate the rules of society.